Current aspects of form generation for unmanned vertical take off vehicles - Kurochkin Valery A.; Bystrov Valery G.; Bystrova Elena A. (Архитектон)
We examine the principle of unmanned flying in the design of vertical takeoff vehicles as an effective way to solve the problem of development and interaction among remote territories of Russia, especially its northern regions. The influence of technological and geoclimatic aspects on the generation of form for unmanned aerial vehicles is considered based on domestic and international developments and student projects on this topic. Systems analysis and environmental approach provide a rationale that the shaping of UAVs for operation in northern conditions to suit the helicopter-type aerodynamic design is the most optimal.